Expert System for Diagnosis of Heart Disease: A Review - Nagar, Suresh; Jain, Arvind Kumar (International Journal of Computer Sciences and Engineering, 2025)
In order to diagnose any disease, the expert system developed by human may be a cheering way out to diminish cost, time, human efforts and medical error. This paper focuses on today’s most severe heart related diseases. It also discusses different expert systems that are presently used in the field of medical sciences. Further, noteworthy contribution is also cited. Additionally, it reveals the well-known database used for heart disease diagnosis i.e. UCI repository.